Relative changes in genetic variability and correlations in an earlymaturing maize population during recurrent selection - Badu-Apraku, Baffour; Akinwale, R.O.; Fakorede, M.A.B.; Oyekunle, M.; Franco, J. (Springer, 2012)
Four cycles of S1 family recurrent selection to improve grain yield and resistance to Striga hermonthica have been completed in TZE-Y Pop STR C0. In order to determine whether or not to continue with the recurrent scheme, it was desirable to evaluate the amount of residual genetic variance and associated parameters in the population. The objective of this study was to characterize the relative changes in the levels of the genetic variances, heritability estimates and genetic correlation coefficients, and to predict future gains from selection for grain yield, Striga resistance and other agronomic traits. Fifty S1 families, derived from each cycle, were evaluated under Striga-infested and Striga-free conditions at Mokwa, Ikenne and Abuja, Nigeria, in 2005 and 2007. Under Striga infestation, genetic variances for grain yield, days to anthesis, plant height and Striga damage generally increased in the advanced cycles of selection. In contrast, the genetic variances for days to silk, anthesis–silking interval, ears per plant, ear aspect and number of emerged Striga plants decreased with selection. The advanced cycles of selection significantly out-yielded the original cycle in both research environments. Heritabilities for grain yield, Striga damage and number of emerged Striga plants were significantly greater than zero. The realized gains from selection for grain yield under Striga infestation (52 kg ha−1 cycle−1) and Striga-free conditions (130 kg ha−1 cycle−1) were remarkably lower than the predicted gains (350 and 250 kg ha−1 cycle−1, respectively). Adequate genetic variability exists in cycle 4 of the scheme to ensure future gains from selection.